Predicting CO2 Permeation through an Enhanced Ionic Liquid Mixed Matrix Membrane (IL3M) - Dzeti F. Mohshim; Hilmi Mukhtar; Binay K. Dutta; Zakaria Man (International Journal of Chemical Engineering)
Ionic liquid mixed matrix membranes (IL3Ms) were synthesized using polyethersulfone (PES) as the base polymer and silica-aluminophosphate (SAPO-34) as the dispersed particles, and their CO2 permeation was investigated. Three of the most widely used models for gas separation—the Maxwell, Lewis–Nielson, and Maxwell–Wagner–Sillar (MWS) models—were then applied to the membranes. Large deviations were found between the model predictions and experimental data. FESEM images suggested that local agglomeration and disorientation of the SAPO-34 particles within the membrane afforded substantial changes in the morphology. The MWS model, which considers the shape factor, was modified to incorporate the volume fraction of the wetted dispersed phase and the ideal shape factor. A direct relationship was found between the filler concentration and the shape factor. The modified model was shown to produce absolute and relative errors of less than 3%. When validated against data from the literature, the deviation remained within 5%. The modified model can be used to estimate the gas permeance of an IL3M.